Numerical Solutions with Linearization Techniques of the Fractional Harry Dym Equation - Yokuş, Asıf; Gülbahar, Sema (Applied mathematics and nonlinear sciences, 2019)
In this study, numerical solutions of the fractional Harry Dym equation are investigated. Linearization techniques are utilized for non-linear terms existing in the fractional Harry Dym equation. The error norms and are computed. Stability of the finite difference method is studied with the aid of Von Neumann stabity analysis.